The role of social programs in the implementation of corporate social responsibility - P. S. Shcherbachenko; I. V. Kryukova (Вестник университета)
In recent years, the role of non-material factors in economic development has been growing: social policy and corporate social responsibility of companies are becoming increasingly important. Determining the forms, methods and amounts of contribution to the socio-economic component ofpublic relations is the prerogative of any company, and structuring activities in this area is a prerequisite for creating social programs. The study is devoted to the definition and justification of the role of social programs in the implementation of corporate social responsibility. The relevance of the research is due to the increasing influence of corporate social responsibility on the economic condition and development of companies, as well as on the socio-economic life of society. The constant interest of all interested parties in the disclosure of corporate information, including social orientation, further confirms the relevance of this study.